2016
DOI: 10.1038/ncomms11724
|View full text |Cite|
|
Sign up to set email alerts
|

NFATc1 supports imiquimod-induced skin inflammation by suppressing IL-10 synthesis in B cells

Abstract: Epicutaneous application of Aldara cream containing the TLR7 agonist imiquimod (IMQ) to mice induces skin inflammation that exhibits many aspects of psoriasis, an inflammatory human skin disease. Here we show that mice depleted of B cells or bearing interleukin (IL)-10-deficient B cells show a fulminant inflammation upon IMQ exposure, whereas ablation of NFATc1 in B cells results in a suppression of Aldara-induced inflammation. In vitro, IMQ induces the proliferation and IL-10 expression by B cells that is blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 63 publications
3
45
0
4
Order By: Relevance
“…Interestingly, psoriasis is associated with low levels of dermal IL-10 and is clinically responsive to locally administered IL-10 (89, 90), possibly reflecting a niche for regulation by IL-10 + cell types such as IL-10 + Bregs. Extending the mouse studies that demonstrate a critical role for IL-10 + B cells in suppressing psoriasiform inflammation (83,84), individuals with psoriasis have reduced numbers of IL-10 + B cells in their blood (91,92). Other cutaneous inflammatory diseases, such as the skin-blistering disease pemphigus and scleroderma, can also be associated with reduced numbers of circulating IL-10 + Bregs during active disease (93)(94)(95)(96) and an increase in disease remission (97).…”
Section: Cutaneous Regulatory B Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, psoriasis is associated with low levels of dermal IL-10 and is clinically responsive to locally administered IL-10 (89, 90), possibly reflecting a niche for regulation by IL-10 + cell types such as IL-10 + Bregs. Extending the mouse studies that demonstrate a critical role for IL-10 + B cells in suppressing psoriasiform inflammation (83,84), individuals with psoriasis have reduced numbers of IL-10 + B cells in their blood (91,92). Other cutaneous inflammatory diseases, such as the skin-blistering disease pemphigus and scleroderma, can also be associated with reduced numbers of circulating IL-10 + Bregs during active disease (93)(94)(95)(96) and an increase in disease remission (97).…”
Section: Cutaneous Regulatory B Cellsmentioning
confidence: 99%
“…In mouse models, IL-10 + Bregs (also known as B10 cells) limit inflammation in cutaneous hypersensitivity (81,82), scleroderma (59), and psoriasis-like inflammation (83,84). Earlier studies suggested that splenic Bregs suppress T cell priming and/or polarization in the initiation phase and that innate-like Bregs (e.g., peritoneal B-1 B cells) are important in the remission phase of inflammation, with all Bregs acting within lymphoid tissues (81,82).…”
Section: Cutaneous Regulatory B Cellsmentioning
confidence: 99%
“…Mice received a daily topical dose of 40 mg 5% IMQ cream (Beselna Cream; Mochida Pharmaceutical, Tokyo, Japan) on the shaved back for 5 consecutive days. The severity of inflammation of the back skin was measured by an objective scoring system based on the clinical PASI (Alrefai et al, 2016). Subcutaneous vessels were measured by ImageJ software (National Institutes of Health, Bethesda, MD).…”
Section: Imq-induced Psoriasis Modelmentioning
confidence: 99%
“…The development of psoriasis-like skin inflammation was reported as a side effect of IMQ application (Wu et al, 2004), and IMQ-induced psoriasis-like murine model has been established to study human psoriasis (van der Fits et al, 2009). The topical application of IMQ-containing cream to the skin of mice is now widely accepted as a convenient and cost-effective murine model for studying early events of psoriasis (Alrefai et al, 2016;van der Fits et al, 2009;Zanvit et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Among the cellular mediators, the crucial role of DCs and T cells (mostly gd T cells) in the development of IMQ-induced psoriasis has been elegantly demonstrated in several recent papers [13,16,[19][20][21][22]. By contrast, B cell-derived IL-10 has been suggested to play a protective role in the same model [23,24]. In terms of mechanisms of action, IMQ-induced psoriasiform skin inflammation primarily involves TLR7-and MyD88-dependent signaling [10], even though a contribution of MyD88-independent mechanisms (e.g., inflammasome activation by the vehicle) to this disease model has also been reported [25].…”
Section: Introductionmentioning
confidence: 99%